Specific molecular targets to control tropical diseases - Rodriguez, Juan Bautista (2001)
Chagas' disease or American trypanosomiasis is considered by the Word Health Organization to be one of the important tropical parasitic diseases worldwide together with malaria and schistosomiasis. The etiologic agent of this illness is the kinetoplastid protozoon Trypanosoma cruzi. The present chemotherapy for the treatment of Chagas' disease remains unsolved. The drugs currently in use are old, ineffective and toxic. Bearing in mind the metabolic differences between the parasite and the mammalian host, some attractive interesting molecular targets for drug design are presented.